Problem Based Learning: Suatu Upaya Meningkatkan Prestasi Belajar Las SMAW Siswa SMK - Khoerudin, Apip; Refiadi, Gunawan (Fakultas Teknik Universitas Negeri Malang, 2020)
Optimization of SMAW learning is necessary for vocational school students to achieve optimal competence. Problem-Based Learning (PBL) was reported in increasing skill learning outcomes. However, a specific PBL treatment in SMAW subjects has not yet published. This research contributed to how to give the SMAW learning method through the PBL model. This research adopted the conventional model as a control of the PBL experiment model. This research applied quasi-experiment with a population of the X-th grade of the VHS students. The samples were X-Mechanical and X-Automotive class, respectively. To amplify the success of the PBL model, the research visually analyzed the students' weldment results based on the surface quality appearance. PBL model increased the study outcome capabilities of the SMAW method up to 17.5 percent (from 75.9 percent to 93.4 percent). This increment was 30.6 percent higher than the conventional method. Statistical evident showed that the PBL index gain on the t-test (a equals 5 percent) was better and followed by a better physical fact in weld surface quality at the weldment area than the conventional one